RHEOLOGICAL PROPERTIES AND THERMAL STABILITY OF CAST COMPOSITIONS BASED ON POLYPHENYLENESULPHIDES - A. B. Baranov; I. N. Tsapenko; A. V. Petrogradsky; I. D. Simonov-Emelyanov; N. L. Shembel (Тонкие химические технологии, 2017)
The rheological properties of polysulfide (PPS) melts and composite materials based on them were investigated in a wide range of temperatures and concentrations of fillers of different nature. It was established that the introduction of rheological additives into dispersed and hybrid-filled composite materials allows significantly reducing the viscosity and improving the processability of the compositions. Introduction of heat-stabilizing additives into PPS allows expanding the temperature interval of processing the composite materials based on PFC from 320 to 340°С. Complete thermal stability curves for the PPS compositions in a wide temperature range were obtained.